Integrated Remote Sensing for Enhanced Drought Assessment: A Multi‐Index Approach in Rajasthan, India - Vivek Agarwal; Bhanwar Vishvendra Raj Singh; Stuart Marsh; Zhengyuan Qin; Anjan Sen; Khusbhu Kulhari (Earth and Space Science)
Abstract This study investigates land use, land cover (LULC) changes, vegetation health, and drought severity in Rajasthan, India, from 1985 to 2020 using remote sensing techniques. By analyzing satellite imagery with the normalized difference vegetation index (NDVI), temperature condition index (TCI), vegetation condition index (VCI), and NDVI deviation (Dev_NDVI), we assess the spatial and temporal dynamics of the region's landscape and drought conditions. Our findings indicate significant LULC changes, including a decrease in water bodies from 6412.87 to 2248.51 km2 and dense forests by 61.37%, while built‐up areas expanded by 890.50%, reflecting substantial human impact and environmental change. Drought analysis revealed that nearly 49% of the study area experienced moderate to severe drought conditions, with VCI levels below 40%, indicating widespread drought impact across different regions and time periods. The study employs weighted sum analysis of Dev_NDVI, VCI, and TCI to create a detailed drought severity map, revealing areas of severe and extreme drought that necessitate immediate action for sustainable management. The novelty of this approach lies in its integrated multi‐index method for assessing drought over a 35 year period, providing a robust framework for analyzing environmental dynamics and the resilience of ecosystems to climatic stresses. This research emphasizes the value of remote sensing for continuous environmental monitoring and highlights future implications for integrating advanced satellite technologies to enhance drought management strategies, ultimately informing policy decisions for sustainable land and water resource management in Rajasthan and similar semi‐arid regions globally.